2004
DOI: 10.1111/j.1472-765x.2004.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Salmonella spp. and Listeria monocytogenes on plastic surface

Abstract: Aims: To investigate the biofilm formation by 122 Salmonella spp. and 48 Listeria monocytogenes strains on a plastic surface. Methods: Quantification of biofilm formation was performed in brain heart infusion (BHI), trypcase soya broth (TSB), meat broth (MB) and 1/20 diluted trypcase soya broth (1/20-TSB) in plastic microtitre plates. Results: All tested Salmonella spp. and L. monocytogenes strains produced biofilm in a suitable medium. However, the quantities of biofilm produced by Salmonella spp. were greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
422
2
32

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(478 citation statements)
references
References 23 publications
22
422
2
32
Order By: Relevance
“…Biofilm formation for all 337 isolates was assessed using the semi-quantitative adherence assay (Stepanović et al 2004;Peeters et al, 2008). The optical density (OD) obtained at 630 nm using a Sunrise Absorbance Reader (PerkinElmer, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation for all 337 isolates was assessed using the semi-quantitative adherence assay (Stepanović et al 2004;Peeters et al, 2008). The optical density (OD) obtained at 630 nm using a Sunrise Absorbance Reader (PerkinElmer, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In a number of experimental studies, the ability of Salmonella to form BF on a variety of materials such as concrete, glass (Prouty and Gunn, 2003), cement (Joseph et al, 2001), stainless steel (Oliveira et al, 2007), plastic (Stepanović et al, 2004;Solomon et al, 2005), granite and rubber (Arnold and Yates, 2009) was confirmed (Solano et al, 2002;Steenackers et al, 2012). Salmonella spp.…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%
“…Biofilm formed in food processing environments is of special importance as it has the potential to act as a chronic source of microbial contamination that may lead to food spoilage or transmission of diseases, and bacteria in biofilms exhibit enhanced resistance to cleaning and sanitation (12).…”
Section: Introductionmentioning
confidence: 99%
“…Formation and presence of biofilm have been investigated by different quantification methods, among which the microtiter plate system is widely used (1,12,14). Microtiter plate systems for quantifying biofilm formation have been investigated using many different organisms and stains (1, 2, …”
Section: Introductionmentioning
confidence: 99%